Memanfaatkan Peluang Pasar dengan Kreativitas: Pembuatan Sambal Rebon Homemade sebagai Peluang Usaha Bagi Generasi Muda dan Ibu Rumah Tangga Di Kelurahan Manulai II Kecamatan Alak Kota Kupang - Hege, Marselinda A.; Kretisana Jagi; David R.E.Selan; Stefanus Reinati; Lende Dangga; Jhon S.D.Liem; Jendri Kadek; Kornelius Dju Jani; Gavar; Aplonia Atto; Astrid Aryani Ndun; Nur aini Bunyani (Universitas Mataram, 2025)
This community service initiative aims to empower young generations and housewives in Manulai II Village, Alak District, Kupang City, through the development of homemade shrimp paste sambal production as a creative economic opportunity. In the context of contemporary economic dynamics characterized by digitalization and changing consumption patterns, the micro-culinary sector offers significant potential for empowerment, although young generations and housewives often face limitations in access to technical knowledge, capital, and marketing strategies. Based on data from the Central Statistics Agency of East Nusa Tenggara Province (2023), the fisheries sector contributes 12% to the regional GRDP, with abundant rebon fish production that has not yet been fully utilized innovatively. The main objectives of the activity are to enhance creative skills in shrimp paste sambal production, form independent micro-business groups, and contribute to inclusive local economic growth. The applied methods include a participatory approach with stages of preparation, training, mentoring, and evaluation over six months, involving 30 participants and collaboration with local stakeholders. The results indicate a 75% increase in technical knowledge, the formation of 3-5 independent business groups with an initial sales volume of 200 kg per month, and an average 20-30% increase in household income. The discussion highlights the effectiveness of Freire's (1970) model in critical education and the relevance of Schumpeter's (1934) innovation theory in opening new market opportunities. The conclusion emphasizes that this initiative strengthens community economic resilience and supports sustainable development agendas, with recommendations for long-term monitoring to ensure business sustainability.